Health shocks and risk aversion: Panel and experimental evidence from Vietnam - Jan Priebe; Ute Rink; Henry Stemmler (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2019)
This paper looks at individual risk behavior and disability in Vietnam, where many households live with a disabled family member. Due to the Vietnam war, disability is a common phenomenon and shapes individuals' daily life and decision making. Using longitudinal data of 2200 households in Vietnam and an instrumental variable strategy, we show that individuals who live with a disabled family member are more risk averse than others. In addition we employ field experiments and psychological primes to elicit risk and loss behavior of individuals living in the Vietnam province Ha-Thinh. The experimental results, underpin our panel results. We show in addition that a negative recollection of health issues, leads to a lower risk attitude of individuals who do not live with a disabled family member and that individuals who live with a disabled family member are less loss averse. Our findings are causal and contribute to existing studies showing that households who are characterized by higher backward risks are more risk averse than others.
Keywords: D1; I14; Z1; 330; risk; disability; Vietnam